HAPPINESS INDEX AMONG NURSING STUDENTS IN UNIVERSITI TEKNOLOGI MARA - Suzana Yusof; Fatimah Sham; Norhafizatul Akma Shohor; Aisyah Jamalluddin; Naz Azfahanee Rambli; Nur Syamimi Zulkifli (Journal of Islamic, Social, Economics and Development, 2021)
Happiness is a crucial factor in human life. Nursing students' life can be challengingdue to many factors that may contribute to their happiness index. Objective: This study aims toidentify the happiness index among full-time nursing students in UiTM Puncak Alam Campus.Method: A quantitative cross-sectional study was conducted using the set of happinessquestionnaires among nursing students. Result: Findings from the population of 161 nursingstudents indicated that the majority of students rated their happiness index as happy with70.2%. Students' age 20 years old and below were the happiest age group with 71.7%, femalesshowed high happiness index with 72.3%, degree students were happier than diploma studentswith 70.3%, and lastly, students with CGPA range 3.49 and below was the happiest group with71.1%. Conclusion: Conclusively that most of the nursing students in UiTM Puncak AlamCampus were happy although they have to deal with the heavy academic curriculum, manyassignments, and clinical practices of every semester.